Design, fabrication and performance test of a peanut harvesting machine - Omer, Elnougomi A. Gadir; Ahmad, Desa (Universiti Putra Malaysia, 1999)
The development of a Peanut Harvesting Machine has been proposed consisting of adjustable digging v-shaped blade type, followed by a double discs lifter for gripping the loosened plant just above the soil surface, using a series of fingers. The loosened plant reaches a stripping mechanism, consisting of two cylinders with series of screw fingers directly above the concave fingers for separating pods and transfers it to the tank at the end of the machine through a conveyor. Results from the primary tests showed that the machine was found suitable for harvesting peanut in one operation. The total power requirement of a single row machine including the draft requirement is predicted to be approximately 12kw (16 hp).